A retrospective study on non-drug related poisoning in the community among children from south India. Issue 2 (15th March 2017) - Das Adhikari, Debasis; Das, Saibal; Winston A, Blessed; Vazhudhi, Kaysina; Kumar, Aniket; Shanthi FX, Margaret; Agarwal, Indira
ABSTRACT: Objectives : This retrospective study was performed to determine the incidence, demographic distribution, types and outcomes across various non-drug related poisonings among children attending a tertiary care center in south India. Methods : All children from 0-16 years who presented to the Paediatric Emergency Department, Christian Medical College, Vellore with non-drug related poisoning from October 2004 to September 2013 were included. Results : Out of the total 997 cases of poisoning, 629 (63.1%) cases were contributed by chemicals and plants: mainly hydrocarbons (kerosene) 309 (49.1%); organophosphates 72 (11.5%); corrosive acids and alkalis 57 (9.1%); insecticides 51 (8.1%); and plant poisons 20 (3.2%). Males (62.79%) and children < 5 years (77.42%) were mostly affected. Although many children developed complications requiring intensive care unit admissions, the total mortality was only 9 (1.4%). The incidence of poisoning showed a decreasing trend over the last 4 years. Conclusion : This study for the first time gives an elaborative insight on non-drug related pediatric poisoning from a tertiary care center in south India for almost a decade.